STRATEGI PENGEMBANGAN RESTORASI RAWA BUNDER BERBASIS SWOT DI TAMAN NASIONAL WAY KAMBAS: SWOT-Based Bunder Swamp Restoration Development Strategy In Way Kambas National Park - Safe'i, Rahmat; Banuwa, Irwan Sukri; Kaskoyo, Hari; Qurniati, Rommy (Forestry Faculty of Hasanuddin University, 2023)
Restoration is an effort to increase forest function for carrying capacity and maintenance of life support systems. Way Kambas National Park (TNWK) has been doing restoration activities at the Rawa Bunder Resort since 2021. This study aims to determine the strategy for developing the restoration of Rawa Bunder, TNWK. Collecting data through interviews with the parties (community and managers) using a questionnaire; then analyzing using the Strength, Weakness, Opportunity, Threats (SWOT) method. From the analysis results, the average total score on the IFAS matrix is 1.54, and the EFAS matrix is 1.15. These results indicate that the position of internal and external factors in the development strategy of the Rawa Bunder restoration, TNWK is in quadrant one. Thus, the strategy for developing the restoration of Rawa Bunder, TNWK, that must be applied is aggressive, namely by using strength to take advantage of opportunities.